Is extrapulmonary tuberculosis a real problem in Poland? - Kołaczkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2007)
Despite continuous improvement of epidemiological parameters of TB in Poland it still presents a serious diagnostic problem. Tuberculosis could be developed in every place and organ in the human body as an extrapulmonary tuberculosis. Tuberculosis may involve multiple organs such as the pleura, CNS, kidney, pericardium, liver, intestinum and bone. Most cases of extrapulmonary tuberculosis are asymptomatic. Patients often manifest disease within 2 years of the initial infection or many years later, often as a result of comorbid states like malnutrition, kidney insufficiency, diabetes mellitus, old age, AIDS, immunosuppression treatment or neoplasm. Imaging plays a very important role in the detection and treatment of pulmonary and extrapulmonary tuberculosis. Ultrasonography is used in pleural changes. Computed tomography (CT) is used rarely. In extrapulmonary tuberculosis CT, magnetic resonance imaging (RMI) and USG as well as conventional methods are useful. Currently all modern microbiological methods of TB diagnosis are available in Poland, such as QuantiFERON® – TB Gold. The treatment of extrapulmonary tuberculosis is proceeded according to treatment category III, named “smear-negative pulmonary tuberculosis”, and to administer first line antituberculous drugs. Extrapulmonary tuberculosis in Poland is still a serious diagnostic and therapeutic problem.